Critical teaching practice of the teaching of Shipibo-Konibo to monolingual Spanish in Peru - Torres Castillo, Fernando Aarón (2022)
This research shows the teaching practice of the teachers of the action-research project carried out with Spanish-speaking students for the teaching of Shipibo-Konibo as a second language at a basic level. The state of the Shipibo-Konibo language is described together with the current situation of the indigenous communities that speak that language; then, a brief summary of the project and the methodological aspects that were applied in the clases is presented. Finally, the issues that emerged from the analysis of teaching practice be announced.